Use of Artificial Intelligence in advertising strategies: a case study of micro-advertising agencies in Ibarra, Ecuador - Vinueza, Jefferson Israel (2024)
This study examined the progressive adoption of artificial intelligence (AI) in the Ibarra advertising sector, specifically focusing on the city’s micro-advertising agencies. Through a quantitative methodological approach and a census technique, surveys were used to evaluate the level of AI integration, the type of resources most used, and the professionals’ perceptions about this emerging technology, contrasting the results with expert interviews and other research. The findings indicate an increase in AI adoption, with chatbots identified as the most prevalent tool, facilitating personalized interactions that enhance user experience and the effectiveness of advertising campaigns. While implementation challenges are acknowledged, they do not represent an insurmountable obstacle; micro-agencies adapt to AI to maintain their competitiveness and market presence. AI is anticipated to have a transformative impact on the local advertising industry, driving significant improvements in efficiency and effectiveness. This study provides valuable insight into the adoption and application of AI in advertising in Ibarra, offering critical perspectives for future strategies and developments in the sector.